Effect of the protein corona formation on antibody functionalized liquid lipid nanocarriers - Navarro-Marchal, Saúl; Martín Contreras, Marina; Castro-Santiago, David; del Castillo-Santaella, Teresa; Graván, Pablo; Jódar-Reyes, Ana Belén; Marchal, Juan Antonio; Peula-García, José Manuel (MDPI, 2023)
The main aim of this study is to report basic knowledge on how a protein corona (PC) could affect or modify the way in which multifunctionalized nanoparticles interact with cells. With this purpose, we have firstly optimized the development of a target-specific nanocarrier by coupling a specific fluorescent antibody on the surface of functionalized lipid liquid nanocapsules (LLNCs). Thus, an anti-HER2-FITC antibody (αHER2) has been used, HER2 being a surface receptor that is overexpressed in several tumor cells. Subsequently, the in vitro formation of a PC has been developed using fetal bovine serum supplemented with human fibrinogen. Dynamic Light Scattering (DLS), Nanoparticle Tracking Analysis (NTA), Laser Doppler Electrophoresis (LDE), and Gel Chromatography techniques have been used to assure a complete physico-chemical characterization of the nano-complexes with (LLNCs-αHER2-PC) and without (LLNCs-αHER2) the surrounding PC. In addition, cellular assays were performed to study the cellular uptake and the specific cellular-nanocarrier interactions using the SKBR3 (high expression of HER2) breast cancer cell line and human dermal fibroblasts (HDFa) (healthy cell line without expression of HER2 receptors as control), showing that the SKBR3 cell line had a higher transport rate (50-fold) than HDFa at 60 min with LLNCs-αHER2. Moreover, the SKBR3 cell line incubated with LLNCs-αHER2-PC suffered a significant reduction (40%) in the uptake. These results suggest that the formation of a PC onto LLNCs does not prevent specific cell targeting, although it does have an important influence on cell uptake.
Keywords: Nanopartículas; Active targeting; Breast cancer; Cellular uptake; Lipid liquid nanocapsules; Protein corona